The effect of rasa rumangsa (self-awareness and empathy) on the subjective burden of families caring for individuals with schizophrenia: Social support as a mediator - Peristianto, Sheilla Varadhila; Subandi, M. A.; Utami, Muhana Sofiati (Psikohumaniora: Jurnal Penelitian Psikologi, 2025)
Families caring for schizophrenic individuals experience pressure due to their associated roles and responsibilities, a situation known as subjective burden. Cultural values influence decision-making related to caretaking behavior, including that based on the Javanese value of rasa rumangsa as an adaptive coping mechanism in caregiving contexts. Social support is a factor that helps to reduce the subjective burden of families taking care of schizophrenic individuals. This study examines social support as a mediator in the role of rasa rumangsa in relation to such subjective burden. The quantitative research used surveys for the data collection method, with 112 carer families of schizophrenic individuals chosen for the study by purposive sampling. The questionnaires used were 1) the Rasa Rumangsa Scale; 2) the Interpersonal Support Evaluation List (ISEL); and 3) the Zarit Burden Interview (ZBI). The hypothesis was tested using Jamovi version 2.6.13 with the medmod module, following Model 4 of Hayes' simple mediation framework. The results indicate that social support fully mediates the relationship between rasa rumangsa and the subjective burden of families caring for individuals with schizophrenia (indirect effect: ß = -.1137, p < .05, 95% CI = -.2186, -.0105). The implication of studying rasa rumangsa as a cultural coping mechanism can be an alternative way of explaining its relationship with the subjective burden of such families. In addition, the findings could also be used to develop mental health programs to improve social support, which will ultimately reduce the subjective burden.